Needs Analysis of Integrating Research and Community Service Into Learning at Islamic Higher Education Institutions - Rahmat Rifai Lubis; Muhammad Ali Hanafiah; Khotimatul Majidah S; Ismi Fauziah; Nana Mahrani (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study aims to analyze the need to integrate research and community service into learning at Islamic higher education institutions through case studies at UIN Sumatera Utara, UIN Syarif Hidayatullah Jakarta, and UIN Sunan Gunung Djati Bandung. The study employed a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, and document analysis involving institutional leaders, academic administrators, research and community service managers, lecturers, and students. Data were analyzed through data condensation, data presentation, and conclusion drawing, while data validity was ensured through source triangulation, methodological triangulation, and member checking. The findings indicate that the three universities have strong institutional foundations for developing the integration of the three pillars of higher education, although their implementation readiness varies. Integration requires institutional mechanisms that connect research and community service units with faculties, study programs, lecturers, and students. Lecturer readiness encompasses not only research competence but also pedagogical capacity to integrate research findings and community service experiences into learning. Students require strengthened academic literacy, research skills, collaboration, and field experience. The integration of the three pillars of higher education should be systematically developed through policies, coordination, human resource capacity building, and sustainable institutional support.